Strategy for the development and promotion The Penaban Lontar Library Museum, Karangasem-Bali to increase tourist visits - Ni Luh Putu Yati Artini; Francisca Titing Koerniawaty (Enrichment : Journal of Management, 2023)
The Dukuh Penaban Traditional Village community initiated the construction of the Dukuh Penaban Lontar Library Museum in Karangasem Regency, Bali, to collect, store, preserve, and present the local community’s lontar works and empower the community at large. The goal of this study is to explain how the Dukuh Penaban Lontar Library Museum is being developed, promoted, and made to attract more tourists. Descriptive qualitative research was used for this project. This writing draws on interviews, observations, and documentation for its data. A plan for the growth and promotion of the Dukuh Penaban Lontar Library Museum has been developed as a result of this writing, which includes the following: Special interests are used to package products for tourist attractions; online media are used to promote them; homestays, restaurants, international-standard public restrooms, and souvenir shops are developed; directions are added; and human resources training is provided.